A short review of recent advancements in PCM-air hybrid thermal management for batteries - Muppana, Veera Nagendra; Samykano, Mahendran; Wan Azmi, Wan Hamzah; Kadirgama, Kumaran; Suraparaju, Subbarama Kousik (Malaysian Institute of Chemistry, 2024)
This comprehensive review paper provides an in-depth overview of Phase Change Materials (PCMs) and air-cooling technologies used for Battery Thermal Management Systems (BTMS). PCMs can be classified by their phase change and by their composition, and each class shows different advantages that respond to complex needs, dissipating the heat in a battery. Organic PCMs based on paraffin, such as 1-Tetradecanol, help improve the efficiency and sustainability of the cooling system. In contrast, paraffin wax offers the high thermal conductivity and stability needed for these applications. Eutectic and composite PCMs are a “made to measure” solution for these needs, and the addition of a PCM to the air cooling is highly advantageous for the optimization of the performance of the battery. It shows the validity of the air cooling in the BTMS, a system intrinsically, cost-effective, and practical in dissipating heat, thus minimizing the thermal stress in the battery. Besides PCM, the paper underscores the critical role of air cooling in improving battery lifespan, safety, and overall performance. The survey reports that air cooling is the leading BTMS configuration in addressing thermal challenges. Air cooling in combination with PCM is a significant approach in this thermal management arena. Among all existing configurations, the encapsulated PCM, metal fins, and the air-cooled hybrid system exhibited the best performance. Each resulted in an overall reduction in the battery’s maximum temperature and a uniform temperature distribution across the entire battery. This review mainly focused on the BTMS using PCMS and air cooling.